2009
DOI: 10.1042/bj20081950
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3,5-bisphosphate and Fab1p/PIKfyve underPPIn endo-lysosome function

Abstract: PtdIns(3,5)P(2) is one of the seven regulatory PPIn (polyphosphoinositides) that are ubiquitous in eukaryotes. It controls membrane trafficking at multiple points in the endosomal/lysosomal system and consequently regulates the size, shape and acidity of at least one endo-lysosomal compartment. PtdIns(3,5)P(2) appears to exert this control via multiple effector proteins, with each effector specific for a subset of the various PtdIns(3,5)P(2)-dependent processes. Some putative PtdIns(3,5)P(2) effectors have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
207
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(215 citation statements)
references
References 123 publications
(249 reference statements)
8
207
0
Order By: Relevance
“…PtdIns(3)P localizes to early endosomes and multivesicular bodies (Gillooly et al, 2000;Gillooly et al, 2003). PtdIns(3,5)P 2 is implicated in late endosomal/lysosomal function, although early endosomal effects have also been described (Dove et al, 2009). The evidence for the subcellular distribution of MTMs to early or late endosomal compartments is conflicting, in part due to a general problem in generating specific immunoreactive MTM antibodies (Robinson and Dixon, 2006), so that most reports have relied on recombinant MTM overexpression to evaluate enzyme subcellular localization.…”
Section: Introductionmentioning
confidence: 95%
“…PtdIns(3)P localizes to early endosomes and multivesicular bodies (Gillooly et al, 2000;Gillooly et al, 2003). PtdIns(3,5)P 2 is implicated in late endosomal/lysosomal function, although early endosomal effects have also been described (Dove et al, 2009). The evidence for the subcellular distribution of MTMs to early or late endosomal compartments is conflicting, in part due to a general problem in generating specific immunoreactive MTM antibodies (Robinson and Dixon, 2006), so that most reports have relied on recombinant MTM overexpression to evaluate enzyme subcellular localization.…”
Section: Introductionmentioning
confidence: 95%
“…Significantly less clear are the mechanistic details of how the PtdIns3P to PtdIns(3,5)P 2 conversion controls the lysosomal sorting process and the relevant downstream targets of the lipid PtdIns(3,5)P 2 (377). It is well established that Fab1p deleted yeast strains have huge vacuoles and impaired transport of CPY to the vacuole (498).…”
Section: Ptdins3p and Ptdins(35)p 2 In Endomembranesmentioning
confidence: 99%
“…It has been shown that all type I IFN-inducing TLRs signal from the endolysosome (22). We hypothesized that intracellular TLR/ligand interaction may be compromised by PIKfyve inactivation because PIKfyve and its product PI(3,5P) 2 are regulators of endolysosome membrane traffic (23); that is, inhibition of PIKfyve could affect endosomal pH or cause a defect in ligand or receptor translocation in endolysosomes.…”
Section: Inactivation Of Pikfyve By Apilimod Selectively Inhibits Tlrmentioning
confidence: 99%